Effectiveness of armrest prototype on muscle activity among male motorcyclists - Alias, Ayuni Nabilah; Karuppiah, Karmegam (2023)
Introduction: Motorcycle is one of the main transports in Malaysia that has been used for decades either for daily life activities or for working. Motorcyclist is the most important element when issues that are related to motorcycle. Therefore, this study will be able to provide evidence to reduce level electromygraphy (muscle activity) with the intervention of armrest prototype which indirectly reduce riding discomfort during prolonged riding process.Method: In 2 different sessions (with and without armrest), 102 respondents were instructed to ride a motorcycle for 2 hours in a laboratory with riding simulator system. The video screen presented by projector a view as motorcyclist in road scenery with computer generated video simulating daytime riding condition. Besides that, Electromyography (EMG) signals were used to assess recorded muscle activity for the right and left arm with the surface of electrode attached. Results: Muscle activity of respondents showed that there are reductions of electromyography levels for both right and left arm’s muscles. There is a positive effect of exertion changes (%) on the flexor carpum radialis (right=24.54%, left=23.98%) and flexor carpum ulnaris (right=8.18%, left=10.62%) muscles of both arms with usage of prototype.